Penggunaan Metode Inkuiri Dalam Peningkatan Hasil Belajar Bahasa Inggris Di Kelas Vii Madrasah Tsanawiyah Muhammadiyah 17 Paciran - M. Chotibuddin; Idzi’Layyinnati; Bahrus Surus (STIT Muhammadiyah Paciran Lamongan, 2017)
Abstract: The Using Inquiry Methods in Increasing Result of Mathematic Study in five grade of Islamic Junior High School. The purpose of this research were (1) to describe steps of inquiry method in increasing result of mathematic study in five grade of Elementary School, (2) identify constraints and solutions using inquiry methods in increasing result of mathematic study in five grade of state elementary school. This research is classroom action research (CAR) conducted in three cycles, each cycle includes the planning, implementation, observation and reflection. The data were analysis using Miles and Huberman interactive model consist of three components are: data reduction, data display, and conclusion drawing/verification. The results showed that (1) the steps of inquiry method can be run apropriate to the scenario, (2) the using inquiry method can increasing result of mathematic study in five grade of Elementary School. Increasing result of mathematic study from pre-test were 40%, in the first cycle were 60%, in the second cycle were 73% and the third cycle increase until 80%